Virtual prototype and field test study on hydraulic brake system performance of mining truck. (June 2019) - Fan, Xiaobin; Gan, Jing
In order to study the braking performance of mining dump truck, the modeling of the oil–gas suspension, front and rear brake of the dump truck were carried out first. Then the virtual prototype model of the dump truck was established in multibody dynamic simulation software. The simulation of braking and emergency braking performance, brake deviation on the flat road, and 9% downhill road were carried out. The brake in driving performance, emergency brake performance, disc brake retardance performance, transmission retardance performance, and hydraulic braking system response time were carried out by the real vehicle experiment, respectively. The result shows that the clearance elimination and pressure rise time of braking system are slightly long, especially the clearance elimination time, so the oil system should have an improvement. At the same time, the braking force distribution of the front and the rear is not reasonable, and the front wheel braking torque is slightly insufficient. After solving these problems by authors' project team, the braking performance of the mine dump truck has been improved significantly.